â€œMargin Pemasaran Bawang Merah Di Desa Tonsewer Kecamatan Tompasoâ€ â€œShallot Marketing Margin in Tonsewer Village Tompaso Subdistrictâ€ - Roosje Kaparang; Octavianus Porajow; Celcius Talumingan; Ellen Tangkere (COCOS, 2015)
ABSTRACK Â The purpose ofÂ  this rescarch is to know the type of marketing channel, to analyze how much cost, profit and marketing margin as well as farmerÂ´s share in each type of shallot marketing channel in Tonsewer Village. This research is carried out for three months. It started from June 2013 and finished in September, 2013.The result of this research shows that the marketing channel occurred in shallot marketing in Tonsewer Village are three type, those are : Marketing channel 1, it is begun from farmer, village collector trader and consumer; Marketing channel 2, it is begun from farmer, village collektor, retailer and consumer; and Marketing channel 3, it is begun from farmer, village collector trader, inter insuler trader and consumer. The marketing channel of shallot in Tonsewer Village that causes cost, prifit and highest marketing channel is in marketing channel 2. The farmerÂ´s share in Tonsewer shows that in the third marketing cennel is the highest.Â